Handbook of Nanoparticles 2015
DOI: 10.1007/978-3-319-13188-7_6-1
|View full text |Cite
|
Sign up to set email alerts
|

Melting Temperature of Metallic Nanoparticles

Abstract: Melting temperature is one of the fundamental properties of materials. In principle, the melting temperature of a bulk material is not dependent on its size. However, as the size of a material decreases toward the nanometer size and approaches atomic scale, the melting temperature scales with the material dimensions. The melting temperature of a nanomaterial such as nanoparticles (isotropic) and nanorods/nanowires (anisotropic) is related to other fundamental physical properties for nanomaterial applications, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…39 Decreasing the size of materials down to the nanometer range also leads to a decreasing melting temperature. 40 By applying the thermodynamic model to calculate the melting temperature for NWs derived by Sar et al , 41 the nano-size copper has a melting temperature of around 1010 °C. This is in accordance to our experiments, as we do not observe the formation of liquid phases.…”
Section: Resultsmentioning
confidence: 99%
“…39 Decreasing the size of materials down to the nanometer range also leads to a decreasing melting temperature. 40 By applying the thermodynamic model to calculate the melting temperature for NWs derived by Sar et al , 41 the nano-size copper has a melting temperature of around 1010 °C. This is in accordance to our experiments, as we do not observe the formation of liquid phases.…”
Section: Resultsmentioning
confidence: 99%
“…Among the physical properties of materials that are affected by size reduction to the nanoscale is the melting point, which is generally found to be lower than their bulk melting point, T m . The reduction of the melting point of nanoparticles (NPs) from T m is attributed to the increased number of surface atoms at the expense of core atoms. For instance, Buffat and Borel found that the melting point of gold NPs could be hundreds of degrees less than the T m of gold .…”
Section: Introductionmentioning
confidence: 99%
“…Solids with reduced dimensionalities, such as nanoparticles (NPs), have properties that can deviate from their bulk materials. Among the properties that depend on size is the melting point, which is reduced with NP size. Understanding the melting of NPs is important for the development of better models of phase transitions at the nanoscale and for the applications of NPs at elevated temperatures. When the size of a solid particle decreases, its surface-to-volume ratio increases.…”
Section: Introductionmentioning
confidence: 99%